Two-sided lid-driven cavity flow at different speed ratio by lattice Boltzmann method - Che Sidik, Nor Azwadi (Trans Tech Publications, 2014)
In this study, the Lattice Boltzmann method has been used to investigate flow configuration of the two-sided lid driven cavity. The top and bottom lid were moved at the same direction but with different speed ratio which varies from 0 to 1. The range of Reynolds number is 100,400 and 1000. The results show that the increase in both speed ratio and Reynolds number give an effect on flow configuration of the cavity.